Intelligent clasification sewage treatment plant (STP) using E-nose - Fatin Munirah, Nasarudin; Muhammad Sharfi, Najib; Suhaimi, Mohd Daud; Mujahid, Mohamad; Saiful Nizam, Tajuddin; Che Mohd Aizal, Che Mohd (Penerbit UMP, 2020)
The environment is an invaluable gift. In an era of progress, economic activities and development projects are often carried out to improve living standards and keep pace with other developed countries. However, this activity has had a negative impact on the environment because some parties still fail to control the disposal of waste that can cause environmental pollution. The effects of this pollution can give to discomfort and disruption to the life of the community. It is because the effects of toxic emissions have caused air pollution to spread foul odors. Therefore, this study was conducted to classify air odor and water odor from the treatment plant in the area of Universiti Malaysia Pahang, Gambang Campus. The classification of air and water odors was done using case-based reasoning.